Association between chemical components of PM2.5 and children's primary care night-time visits due to asthma attacks: A case-crossover study - Shin Yamazaki (Allergology International, 2019)
Background: Few papers have examined the association between the chemical components of PM2.5 and health effects. The existence of an association is now under discussion. Methods: This case-crossover study aimed to examine the association between the chemical components of PM2.5 and night-time primary care visits (PCVs) due to asthma attacks. The subjects were 1251 children aged 0–14 years who received medical care for asthma at a municipal emergency clinic. We measured daily average concentrations of hydrogen ion, sulfate ion, nitrate ion and water-soluble organic compounds (WSOCs), which are components of PM2.5. We estimated the odds ratios (ORs) of PCVs per unit increment (inter quartile ranges) in each chemical component of PM2.5 for the subgroups of warmer months and colder months separately. Results: No association was seen between PCVs and PM2.5 mass concentrations the day before the PCVs in either warmer or colder months. In the warmer months, an association was seen with the concentrations of WSOCs and hydrogen ion the day before the PCVs (OR = 1.33; 95% CI: 1.00–1.76, OR = 1.18; 95% CI: 1.02–1.36, respectively). Furthermore, a negative association was seen between sulfate ion and PCVs (OR = 0.85; 95%CI: 0.74–0.98). No associations were observed in the colder months. Conclusions: We observed a positive association between PCVs and certain concentrations of WSOCs and hydrogen ions in warmer months. In contrast, sulfate ion showed a negative association. Keywords: Air pollution, Asthma, Chemical component, Particulate matter, PM2.5